PREVALENCE OF HEPATITIS B VIRUS AND ASSOCIATED RISK FACTORS IN IRULA TRIBAL POPULATION - Dinesh e, Ramya; S, Ramalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: The study is to analyze the prevalence of infections caused by hepatitis B virus (HBV), and to analyze of risk factors for hepatitis B surface antigen (HBsAg) transmission among the Irula tribes of Tamil Nadu. Methods: Serum samples were collected from 350 participants of Irula tribes from 15 different locations of Tamil Nadu. All serum samples were tested for serological markers of HBV (HBsAg) by 3rd generation enzyme-linked immunosorbent assay kit, and the data were subjected to analyze using SPSS (version 17.0) and Chi-square test to determine the risk factors of HBV among Irula tribes. Results: In the study, HBsAg positivity was observed in a higher percentage in males 10 (8.47%) than females 9 (3.54%) and their all age groups indicate the high prevalence of HBV infection in Irula tribes. Analysis of risk factors showed that jaundice in family (JF), tattooing, series of injection, sexual promiscuity, and surgery with blood transfusion plays a major role in transmission in spread of HBV. Conclusion: Hepatitis B is a major health problem in Irula tribes and needs to design intervention strategies among Irula tribal population.